Error Analysis on Descriptive and Narrative Writing of The Fifth Grade Student’s Indonesian Language Lesson - Aris Wuryantoro; Dwi Rohman Saleh; Rika Prasetya Cahyaningtyas (Universitas Sebelas Maret, 2019)
This research is aimed to describe the error and its causes made by fifth grade students of SDN Bangunrejo Kidul 1 Kedunggalar, Ngawi on descriptive and narratives writing in Indonesian language lessons. The research method was descriptive qualitative to results of descriptive and narratives writing of fifth grade students of SDN Bangunrejo Kidul 1, Kedunggalar, Ngawi on Indonesian language lessons. Data obtained by using observation, interview and documentation technique. Data analyzed through reduction, presentation, and draw conclusions. Research reveals that fifth grade students still have error on descriptive and narrative writing in capital letter, punctuation, and prepositions or passive verb di-. Class V students' error on descriptive and narrative writing are caused by the lack of language rules, accuracy and haste of students in descriptive and narrative writing of Indonesian language.